Tindak Tutur Direktif: Realisasi Tindak Tutur Menyuruh dalam Bahasa Jawa pada Keluarga Penutur Jawa - Ardis Septi E.R; Nurhayati Nurhayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The aim of this article was to know the variation of directive speech acts especially in giving order in Javanese and to know what factors that influence the use of a certain directive form in Javanese. Data were taken from daily conversations of a family in Central Java by using recording and note taking method. The analysis was done by using identity and distributional method. The result of the analysis indicated that in Javanese, directive speech acts were conducted both directly and indirectly. The use of those forms was influenced by age of the speaker, social status of the speaker, and situation. In using directive speech acts-command, the sentences are marked by linguistic and pragmatic devices. Keywords: Speech Act, Directive, Order, Javanese